2009
DOI: 10.1074/jbc.m806501200
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila ABC Transporter, DmHMT-1, Confers Tolerance to Cadmium

Abstract: Half-molecule ATP-binding cassette transporters of the HMT-1 (heavy metal tolerance factor 1) subfamily are required for Cd 2؉ tolerance in Schizosaccharomyces pombe, Caenorhabditis elegans, and Chlamydomonas reinhardtii. Based on studies of S. pombe, it has been proposed that SpHMT-1 transports heavy metal⅐phytochelatin (PC) complexes into the vacuolysosomal compartment. PCs are glutathione derivatives synthesized by PC synthases (PCS) in plants, fungi, and C. elegans in response to heavy metals. Our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 35 publications
6
51
1
Order By: Relevance
“…However, previous studies suggested that GSH instead of PCs is required for SpHMT1 function in yeast (Prévéral et al, 2009;Sooksa-Nguan et al, 2009), in contrast to the current result in Arabidopsis. The inconsistency possibly resulted from the unusual conditions used in yeast, where high abundance of SpHMT1 protein might recognize GSH that is devoid of competition from PCs.…”
Section: Sphmt1-mediated Sequestration Of CD 2+ Requires Pcscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, previous studies suggested that GSH instead of PCs is required for SpHMT1 function in yeast (Prévéral et al, 2009;Sooksa-Nguan et al, 2009), in contrast to the current result in Arabidopsis. The inconsistency possibly resulted from the unusual conditions used in yeast, where high abundance of SpHMT1 protein might recognize GSH that is devoid of competition from PCs.…”
Section: Sphmt1-mediated Sequestration Of CD 2+ Requires Pcscontrasting
confidence: 99%
“…Subsequent studies from overexpression of SpHMT1 also implicated GS2-Cd as a likely substrate when PCs were absent (Prévéral et al, 2009;Sooksa-Nguan et al, 2009). The production of both PCs and GSH can be abolished by BSO that inhibits a key enzyme in GSH biosynthesis (Howden et al, 1995a).…”
Section: Tolerance and Accumulation In Transgenic Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was particularly intriguing after the completion of the Arabidopsis genome project, where it was clear that this reference plant lacks an Hmt1 ortholog, but retains the capacity to sequester PCs and Cd in vacuoles to form HMWCs (30,32). Hmt1-like proteins are not abundant in nature, being restricted to a limited number of organisms, and their function is not completely understood (33). The closest Hmt1 homologues in Arabidopsis are the ATM transporters localized in the mitochondrion (30,31,33,34).…”
mentioning
confidence: 99%